The Effects of the Professional Learning Communities - (:unkn) unknown (DESTECH PUBLICATIONS, INC, 2014)
We are living in an age of globalization and knowledge society and it has brought new roles and burdens on schools. Teachers and school administrators are expected to perform different roles and this clearly show a professional development need for them. Education reformers in the USA has searched ways to restructure schools and they came up with professional learning communities which is considered as the best practice by many education researchers to improve the school as a whole community while diminishing teacher isolation and promoting teacher collaboration and dialog for sharing practices and experiences. Turkish schools are also in need of some change. In the researches that examined the dimensions of professional learning communities and some reports show that Turkish schools need to turn into learning organizations by applying professional learning communities. This can help to reduce the barriers for teacher collaboration and thus help cure the problem of teacher isolation. It is clear from the literature that implementing professional learning communities can improve the effectiveness of Turkish schools and it can lead to better outcomes in student learning which helps them to become successful and lifelong learners.
Keywords: Professional development; professional learning communities; teacher isolation